Talk:The Monad.Reader/Issue3/Notes on Learning Haskell

From HaskellWiki
Jump to navigation Jump to search
The printable version is no longer supported and may have rendering errors. Please update your browser bookmarks and please use the default browser print function instead.

I fail to see, in the first example, why

t :: (Char->Float) -> (Float->Int) -> Char -> Int
t f g c = g . f c

is a 'valid form'. The code is the same as the code above it. Just some variables have been renamed.

It also results in the same error message. Shouldn't this be:

t :: (Char->Float) -> (Float->Int) -> Char -> Int
t f g c = (g . f) c

Or am I missing something obvious?